Rainwater Quality Disparities Across Malaysian Peninsula Sites - Uddin Md.H.; Rokonuzzaman Md.; Nur-E-alam M.; M.soudagar M.E.; Mohamed H.B.; Amin N. (River Publishers, 2025)
This research describes the physicochemical quality of harvested rainwater at four distinct locations in Peninsula Malaysia. The evaluation of rainwater quality across different geographic areas aims to provide valuable insights into potential variations and trends in rainwater quality to reduce water demand globally. This analysis is conducted to determine seven properties, namely ammoniacal nitrogen, biochemical oxygen demand (BOD5), chemical oxygen demand (COD), dissolved oxygen (DO), pH, total dissolved solids (TDS), and turbidity. The results demonstrate that the quality of harvested rainwater meets the raw water quality standards set by the World Health Organization (WHO) and the National Water Quality Standards for Malaysia (NWQSM), indicating good quality rainwater in Malaysia. However, the COD for rainwater in all locations exceeded the limit, with a range of 14.1 to 29.7 mg/L, while the maximum limit for COD set by WHO is 10 mg/L, and according to NWQSM standards, it is 10-100 mg/L. The average pH of the collected rainwater is acidic ranged from 4.7 to 5.56. BOD5 for the collected rainwater is excellent; however, L2 has a slightly higher BOD5 at 6.5 mg/L, whereas the recommended limit by WHO is 6 mg/L, and the NWQSM standard suggests a range of 1-12 mg/L, with a standard limit of 5-7 mg/L. Nevertheless, DO levels ranged from 7.71 to 7.76 mg/L, indicating an ambient gas concentration in the rainwater. The collected rainwater can be used for portable purposes, gardening, smart farming, and toilet flushing. 2024 River Publishers. ? 2024 River Publishers. All rights reserved.